Courtship song genes and speciation in sand flies - SG Oliveira; M Bottecchia; LGSR Bauzer; NA Souza; RD Ward; CP Kyriacou; AA Peixoto (Memorias do Instituto Oswaldo Cruz, 2001)
Lutzomyia longipalpis (Lutz & Neiva, 1912) (Diptera: Psychodidae: Phlebotominae) is a vector of visceral leishmaniasis in the Americas and it might represent a complex of sibling species. Reproductive isolation between closely related species often involves differences in courtship behaviour. cacophony (cac) and period (per) are two Drosophila genes that control features of the "lovesong" males produce during courtship that has been implicated in the sexual isolation between closely related species. We are using gene fragments from L. longipalpis' homologues of these two genes to study the speciation process in this putative species complex.